Preparation method of nanometer silicon oxide low-boiling-point alcohol dispersion liquid
By surface modification and dispersion of nano SiO2 in the liquid phase, combined with the reaction of silane coupling agent and water, the problem of insufficient dispersion of nano SiO2 is solved, and good dispersion and stability of nanoparticles are achieved, the process flow is simplified and the product purity, safety and environmental protection are ensured.
Patent Information
- Application Number
- CN202510293108.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-06-13
AI Technical Summary
In the prior art, nano SiO2 has insufficient dispersion and is difficult to completely disperse in organic solvents, affecting its application performance and range.
Using a silica sol of 8-20nm as raw material, a silane coupling agent is added to react with water by surface modification in the liquid phase and dispersing in low-boiling alcohol. After the reaction, the nano-silica low-boiling alcohol dispersion is obtained without dehydration.
It achieves good dispersion and stability of nanoparticles, the product appearance is clear and transparent, avoids agglomeration problems, simplifies the process flow, and ensures the purity and safety of the product.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a nano-silica dispersion liquid, and in particular to a method for preparing a nano-silica low-boiling alcohol dispersion liquid. Background Art
[0002] Nano-SiO 2 As an important inorganic nano-material that is widely used, due to its rich surface hydroxyl groups, strong hydrophilicity, and relatively high surface energy, nano-particles are extremely prone to agglomeration and difficult to disperse. During actual use, even through shear and ultrasonic dispersion, it is often difficult to truly and completely disperse the particles sufficiently, which affects its application performance and application scope. Therefore, if a dispersion liquid of an organic solvent with excellent dispersibility can be prepared in advance, its performance as a nano-material can be more fully exerted in many applications.
[0003] As a commonly used organic solvent in many conventional applications, low-boiling alcohols have also been reported to be used as dispersants for nano-SiO 2 relatively frequently.
[0004] For example, Chinese Patent CN103101916A, "A Method for Preparing an Alcohol-Dispersed Silica Sol", introduces a process method based on an acidic aqueous silica sol, adding an alcohol solvent (such as methanol, ethanol, etc.), and gradually removing water through an ultrafiltration concentration process to finally obtain an alcohol-dispersed silica sol. However, in this process method, it is necessary to repeatedly add alcohol and perform ultrafiltration concentration steps. Not only is the process cumbersome, but a large amount of alcohol is also prone to bringing safety hazards during the ultrafiltration concentration process. Moreover, a large amount of alcohol-containing aqueous solution is produced as a by-product, and the alcohol needs to be recovered by distillation, further increasing the manufacturing cost and safety and environmental protection hazards.
[0005] Another example is Chinese Patent CNCN109181536B, "A Method for Preparing a Transparent Superhydrophobic SiO 2 Nano-Functional Liquid", which introduces a method using an alcohol solvent as a reaction medium, adding a basic catalyst (such as ammonia water, NaOH aqueous solution, etc.) and a silicate ester, stirring and aging to generate a dispersion liquid of nano-SiO 2 particles. After hydrophobic modification, a low-surface-energy fluorinated organic compound is added to the dispersion liquid of nano-SiO 2 particles for reaction to generate a method for preparing a transparent superhydrophobic SiO 2 nano-functional liquid. This patent method is simple and has a relatively low cost, and can be used on the surfaces of substrates such as glass, ceramics, and metals. However, the product of this process is actually a silane hydrolysis solution with less water added. The microscopic structure of the product is mainly a linear combination freely formed by silanol small molecules generated by silane hydrolysis, lacking a central particle. Therefore, the dispersion liquid obtained by this method has limited applications in other material modification aspects except for being used as a coating film. Summary of the Invention
[0006] The problem to be solved in this aspect is to overcome the deficiencies in the prior art and provide a preparation method for a nano-silica low-boiling-point alcohol dispersion with a simple preparation process and a safe, environmentally friendly process. At the same time, the dispersion has good dispersibility to suit applications in more industries.
[0007] To achieve the above object, the present invention adopts the following technical solutions: A preparation method for a nano-silica low-boiling-point alcohol dispersion, comprising the following steps: (1) Using a silica sol with a silica mass percentage content of 20%-40% as a raw material, adjusting the pH value to 2.0-5.5 with an acid, and then adding a low-boiling-point alcohol, mixing evenly to obtain a mixed solution A; the addition amount of the low-boiling-point alcohol is 1.5-2.5 times the weight of the water in the silica sol; (2) Adding a silane coupling agent to the above mixed solution A to react with the water in the mixed solution. After reacting until the sampled reaction solution can be miscible with butyl acetate in a volume ratio of 1:1 and the mixed solution is transparent and does not separate into layers, continue stirring and reacting for 0-3 hours to obtain a nano-silica low-boiling-point alcohol dispersion; the addition amount of the silane coupling agent is 0.23-0.28 times the amount of water contained in the silica sol in terms of mol; the reaction temperature is 15-55°C.
[0008] The low-boiling-point alcohol is any one or a mixture of any two of methanol, ethanol, and isopropanol. The silane coupling agent is KH560 or KH151 or methyltriethoxysilane or methyltriethoxysilane, or a mixture of two of them. The acid is hydrochloric acid or formic acid or acetic acid, or a mixture of hydrochloric acid and acetic acid, or a mixture of formic acid and acetic acid.
[0009] Adopting the above technical solutions, compared with the prior art, the beneficial effects of the present invention are as follows:
[0010] First, using a silica sol with a particle size of 8-20 nm as a raw material, the entire process of surface modification and dispersion in a low-boiling-point alcohol is completed in the liquid phase, avoiding the agglomeration problem of conventional nano-powders during the drying process, ensuring the dispersibility of the nano-particles in the dispersion, and obtaining a product with good dispersibility of nano-particles and a clear and transparent product appearance. Due to the steric hindrance effect of the linear organic molecular chains grafted on the nano-particles, the stability of the dispersion is ensured, and various dispersants do not need to be introduced, ensuring the purity of the product.
[0011] Second, in the present invention, by adding a silane coupling agent to the silica sol and utilizing the reaction of the silane coupling agent with water, after the reaction is completed, a silica alcohol dispersion can be directly obtained without dehydration operation. At the same time, in this process, as the hydrolysis reaction of the silane coupling agent proceeds, the silane hydrolyzate reacts with the hydroxyl groups on the surface of the silica sol colloid, synchronously realizing the surface modification of the silica sol particles. In this way, by utilizing the steric hindrance effect brought by the organic groups grafted on the particles, without the need for dispersants and stabilizers, the product has good stability and relatively high purity, meeting the usage requirements of different application fields.
[0012] Meanwhile, by selecting different silane coupling agents, different groups can be grafted onto the surface of the colloidal particles to meet different usage requirements.
[0013] Thirdly, the process of the present invention is simple. After one-time feeding, the whole process is completed in a sealed system. The process is concise and efficient, and the process is safe, environmentally friendly, and can meet the process requirements of green production.
[0014] In summary, the preparation method of the nano-silica low-boiling-point alcohol dispersion liquid of the present invention overcomes the deficiencies in the prior art. The preparation process is simple, the process is safe and environmentally friendly, and at the same time, the dispersion liquid has good dispersibility and high product purity, and can be suitable for the applications of more industries. The dispersion liquid produced by this process can be used as a raw material for preparing other medium- and high-boiling-point organic solvent dispersion liquids, or can be directly coated on the surface of cement, etc. to form a ceramic film. Specific Embodiments
[0015] Example 1
[0016] Transfer 100 g of silica sol with a particle size of 8 nm and a content of 20% to a three-necked flask, start stirring (stirring speed 200 r / min), control the reaction temperature at about 40 °C, use a constant pressure dropping funnel to drop hydrochloric acid at a rate of 1 mL / min to adjust the pH value of the silica sol to 2.0, then continue stirring for 15 min, add 200 g of methanol, and then continue stirring for 15 min. Then, add 294 g of KH560 (γ-glycidoxypropyltrimethoxysilane) at a rate of about 10 mL / min, and continue stirring after adding.
[0017] Keep the temperature of the reaction solution at about 25 °C, continue stirring for 12 hours and then take a sample for detection: Take 3 - 5 ml of the sample, add an equal volume of butyl acetate reagent, gently shake the test tube to mix the two liquids, and then let it stand and observe. The mixed liquid does not separate, and it is visually uniform and transparent, indicating that the reaction is basically complete (if the mixed liquid becomes turbid after mixing, continue stirring the reaction, and then take a sample for testing every 2 - 3 hours until the detected mixed liquid is transparent).
[0018] Continue stirring for 3 hours to make the reaction more complete.
[0019] Stop the reaction, observe the dispersion liquid, which is transparent in appearance, and weigh to obtain 592 g of the dispersion liquid. The dispersion liquid has good dispersibility and can be directly coated on the surface of cement, etc. to form a ceramic film.
[0020] According to the method of GB / T 1725-2007 "Determination of Non-Volatile Content of Paints, Varnishes and Plastics" (test conditions: constant temperature at 120 °C for 24 h), the non-volatile content of this dispersion liquid is measured to be 38.3%. The main component of this non-volatile matter is modified nano-silica obtained by grafting organic molecular chains on the surface of nano-silica.
[0021] Example 2
[0022] Transfer 100 g of silica sol with a particle size of 10 nm and a content of 24% to a three-necked flask, start stirring (rotation speed 200 r / min), control the reaction temperature at about 40 °C, and use a constant pressure dropping funnel to drop a mixture of hydrochloric acid and acetic acid with a mol ratio of 1:1 at a rate of 1 mL / min. After adjusting the pH value of the silica sol to 4.0, continue stirring for 15 min, add 175 g of ethanol, and then continue stirring for 15 min. Then, add 217 g of silane A151 (vinyltriethoxysilane) at a rate of about 10 mL / min. After adding, continue stirring.
[0023] Keep the temperature of the reaction solution at about 40 °C, continue stirring for 12 hours and then take a sample for detection: Take 3 - 5 ml of the sample, add an equal volume of butyl acetate reagent, gently shake the test tube to mix the two liquids, and then let it stand and observe. The mixed liquid does not separate layers, and it is visually uniform and transparent, indicating that the reaction is basically complete.
[0024] Continue stirring for 1 hour and then cool naturally.
[0025] Observe the dispersion liquid, which is transparent in appearance. Weigh and obtain 488 g of the dispersion liquid. This dispersion liquid has good dispersibility and can be directly coated on the surface of cement, etc. to form a ceramic film.
[0026] According to the method of GB / T 1725 - 2007 "Determination of non-volatile content of paints, varnishes and plastics" (test conditions: constant temperature at 120 °C for 24 h), it is measured that the non-volatile content of this dispersion liquid is 23.0%. The main component of this non-volatile matter is modified nano-silica obtained by grafting organic molecular chains on the surface of nano-silica.
[0027] Example 3
[0028] Transfer 100 g of silica sol with a particle size of 12 nm and a content of 28% to a three-necked flask, start stirring (rotation speed 200 r / min), control the reaction temperature at about 30 °C, and use a constant pressure dropping funnel to drop formic acid to adjust the pH value of the silica sol to 3.0. After that, continue stirring for 15 min, add 152 g of isopropanol, and then continue stirring for 15 min. Then, add 142 g of methyltrimethoxysilane at a rate of about 10 mL / min. After adding, continue stirring.
[0029] Keep the temperature of the reaction solution at about 30 °C, continue stirring for 12 hours and then take a sample for detection: Take 3 - 5 ml of the sample, add an equal volume of butyl acetate reagent, gently shake the test tube to mix the two liquids, and then let it stand and observe. The mixed liquid does not separate layers, and it is visually uniform and transparent, indicating that the reaction is basically complete.
[0030] Observe the dispersion liquid, which is transparent in appearance. Weigh and obtain 391 g of the dispersion liquid. This dispersion liquid has good dispersibility and can be directly coated on the surface of cement, etc. to form a ceramic film.
[0031] According to the method of GB / T 1725-2007 "Determination of non-volatile content of paints, varnishes and plastics" (test conditions: constant temperature at 120 °C for 24 h), the non-volatile content of this dispersion was measured to be 24.9%. The main component of this non-volatile matter is modified nano-silica obtained by grafting organic molecular chains on the surface of nano-silica.
[0032] Example 4
[0033] Transfer 100 g of silica sol with a particle size of 15 nm and a content of 32% to a three-necked flask, start stirring (rotation speed 200 r / min), control the reaction temperature at about 45 °C, and use a constant pressure dropping funnel to drop a mixed solution of formic acid and acetic acid with a molar ratio of 1:1 at a rate of 1 mL / min. After adjusting the pH value of the silica sol to 4.5, continue stirring for 15 min, add 32.5 g of methanol and 97.5 g of isopropanol, and then continue stirring for 15 min. Then, add 168 g of methyltriethoxysilane at a rate of about 10 mL / min, and continue stirring after adding.
[0034] Keep the temperature of the reaction solution at about 45 °C, continue stirring for 12 hours and then take a sample for detection: Take 3-5 ml of the sample, add an equal volume of butyl acetate reagent, gently shake the test tube to mix the two liquids, and then let it stand and observe. The mixed solution does not separate layers, and it is visually uniform and transparent, indicating that the reaction is basically complete.
[0035] Continue stirring for 2 hours and then cool naturally.
[0036] Observe the dispersion. The appearance is transparent. Weigh and obtain 395 g of the dispersion. This dispersion has good dispersibility and can be directly coated on the surface of cement, etc. to form a ceramic film.
[0037] According to the method of GB / T 1725-2007 "Determination of non-volatile content of paints, varnishes and plastics" (test conditions: constant temperature at 120 °C for 24 h), the non-volatile content of this dispersion was measured to be 24.1%. The main component of this non-volatile matter is modified nano-silica obtained by grafting organic molecular chains on the surface of nano-silica.
[0038] Example 5
[0039] Transfer 100 g of silica sol with a particle size of 18 nm and a content of 36% into a three-necked flask, start stirring (rotation speed 200 r / min), control the reaction temperature at about 35 °C, and use a constant-pressure dropping funnel to drop a mixed solution of hydrochloric acid and formic acid with a molar ratio of 1:1 at a rate of 1 mL / min. After adjusting the pH value of the silica sol to 3.5, continue stirring for 15 min, add 54.5 g of ethanol and 54.5 g of isopropanol, and then continue stirring for 15 min. Then, add 102 g of KH560 (γ-glycidoxypropyltrimethoxysilane) and 59 g of methyltrimethoxysilane at a rate of about 10 mL / min, and continue stirring after adding.
[0040] Keep the temperature of the reaction solution at about 35 °C and continue stirring for 12 hours, then take a sample for testing: Take 3 - 5 ml of the sample, add an equal volume of butyl acetate reagent, gently shake the test tube to mix the two liquids, and then let it stand and observe. The mixed liquid does not separate, and it is visually uniform and transparent, indicating that the reaction is basically complete.
[0041] Observe the dispersion liquid, which is transparent in appearance. Weigh and obtain 367 g of the dispersion liquid. This dispersion liquid has good dispersibility and can be directly coated on the surface of cement, etc. to form a ceramic film.
[0042] According to the method of GB / T 1725 - 2007 "Determination of Non-Volatile Content of Paints, Varnishes and Plastics" (test conditions: constant temperature at 120 °C for 24 h), the non-volatile content of this dispersion liquid is measured to be 37.1%. The main component of this non-volatile matter is modified nano-silica obtained by grafting organic molecular chains on the surface of nano-silica.
[0043] Example 6
[0044] Transfer 100 g of silica sol with a particle size of 20 nm and a content of 40% into a three-necked flask, start stirring (rotation speed 200 r / min), control the reaction temperature at about 55 °C, and use a constant-pressure dropping funnel to drop acetic acid to adjust the pH value of the silica sol to 5.5. After that, continue stirring for 15 min, add 60 g of methanol and 30 g of ethanol, and then continue stirring for 15 min. Then, add 90 g of KH560 (γ-glycidoxypropyltrimethoxysilane) and 73 g of Silane A151 (vinyltriethoxysilane) at a rate of about 10 mL / min, and continue stirring after adding.
[0045] Keep the temperature of the reaction solution at about 55 °C and continue stirring for 12 hours, then take a sample for testing: Take 3 - 5 ml of the sample, add an equal volume of butyl acetate reagent, gently shake the test tube to mix the two liquids, and then let it stand and observe. The mixed liquid does not separate, and it is visually uniform and transparent, indicating that the reaction is basically complete.
[0046] Observe the dispersion liquid, which is transparent in appearance. Weigh and obtain 349 g of the dispersion liquid. This dispersion liquid has good dispersibility and can be directly coated on the surface of cement, etc. to form a ceramic film.
[0047] According to the method of GB / T 1725-2007 "Determination of non-volatile content of paints, varnishes and plastics" (test conditions: constant temperature at 120 °C for 24 h), the non-volatile content of this dispersion was measured to be 38.0%. The main component of this non-volatile matter is modified nano-silica obtained by grafting organic molecular chains on the surface of nano-silica.
[0048] For the 6 specimens prepared in the above Examples 1-6, according to GB / T 6753.3-1986 "Test Method for Storage Stability of Paints", specifically with the temperature controlled at 50 ± 2 °C, they were taken out after being stored for 15 days. Observation: The dispersions of the two specimens in Example 1 and Example 6 showed obvious thickening, but still had a little fluidity, and the appearance was still transparent without sediment; the dispersions of the four specimens in Examples 2-5 did not show obvious thickening, with normal appearance, transparent, without turbidity and sediment.
[0049] Then observe that the appearance and viscosity of the two specimens of the dispersions in Example 1 and Example 6 stored at room temperature are normal. Continue the test: Take the original samples of these two dispersions (samples stored at room temperature) and add 0.25% times of ethanol based on the weight of the dispersion respectively. After stirring evenly, repeat the above-mentioned test method, with the temperature controlled at 50 ± 2 °C and store for 15 days for the test. Observation: The two dispersions supplemented with ethanol did not show obvious thickening, and at the same time, the appearance was normal, transparent, without turbidity and sediment.
[0050] Further test: Mix the 6 specimens prepared in the above Examples 1-6 with butyl acetate (analytical pure) in a weight ratio of 1:1. Observe that the mixed liquids of the 6 specimens are all transparent in appearance and do not separate layers. Then heat to distill off the low-boiling alcohols until no more liquid distills out at about 110 °C, and transparent and uniform nano-silica dispersions can be obtained.
[0051] Based on the above-mentioned situations of the examples, it shows that the dispersibility, dispersion stability and corresponding application performance of the dispersion specimens of the products of the patent process meet the requirements of the invention purpose.
Claims
1. A method for preparing a nano-silicon oxide low-boiling point alcohol dispersion, characterized in that The following steps are involved: (1) using a silica sol having a silica content of 20% to 40% by mass as a raw material, adding acid to adjust the pH value to 2.0 to 5.5, then adding a low-boiling alcohol, and mixing uniformly to obtain a mixed solution A; the amount of the low-boiling alcohol added is 1.5 to 2.5 times the weight of the water in the silica sol; (2) adding a silane coupling agent to the mixed solution A to react with the water in the mixed solution until the reaction solution is miscible with butyl acetate in a volume ratio of 1:1 when sampled and tested, and the mixed solution is transparent and does not separate, and then continuing to stir and react for 0-3 hours to obtain a nano-silicon oxide low-boiling point alcohol dispersion; the amount of the silane coupling agent added is 0.23-0.28 times the amount of water contained in the silica sol in mol; and the reaction temperature is 15-55°C.
2. The method for preparing a nano-silicon oxide low-boiling point alcohol dispersion according to claim 1, characterized in that The low boiling point alcohol is any one of methanol, ethanol and isopropanol or a mixture of any two of them.
3. The method for preparing a nano-silicon oxide low-boiling point alcohol dispersion according to claim 1 or 2, wherein the silane coupling agent is KH560 or KH151 or methyltriethoxysilane or methyltriethoxysilane, or a mixture of two thereof.
4. The method for preparing a nano-silicon oxide low-boiling point alcohol dispersion according to claim 3, wherein the acid is hydrochloric acid, formic acid, acetic acid, a mixture of hydrochloric acid and acetic acid, or a mixture of formic acid and acetic acid.
Citation Information
Patent Citations
Method for preparing alcohol-dispersed silica sol
CN103101916A
Preparation method and application of transparent superhydrophobic and superoleophobic SiO2 nanofluids
CN109181536B